UXJs: Tracking and Analyzing Web Usage Information With a Javascript Oriented Approach - Solís-Martínez, Jaime; Pascual Espada, Jordán; González-Crespo, Rubén; Pelayo García-Bustelo, B. Cristina; Cueva Lovelle, Juan Manuel (IEEE Access, 2020)
Knowing what the user does inside your web and how he does it is crucial nowadays to understand the strengths and inconveniences of your web's design and architectural structure as well as about the usability of the site. Currently, there are several solutions that allow the tracking of the user behavior but these have some limitations due to the information they are able to capture and how they can present that information in a useful way for the web developer. Many of these platforms don't capture information about the user activity in the websites, clicks, mouse movements, etc. Some solutions do capture some of this user activity, but they only process the information visually showing heatmaps. In this paper we present UXJs, a novel research approach for collecting automatically all possible information about the user activity in websites, showing this information quantitatively and allowing its automatic statistical analysis and the rapid understanding by web developers.
Keywords: javascript; statistics; tracking; usability; web; Scopus; JCR